Effect of Dry Eye Disease on the Kinetics of Lacrimal Gland Dendritic Cells as Visualized by Intravital Multi-Photon Microscopy - Ortiz, Gustavo; Chao, Cecilia; Jamali, Arsia; Seyed-Razavi, Yashar; Kenyon, Brendan; Harris, Deshea L.; Zoukhri, Driss; Hamrah, Pedram (Frontiers in Immunology, 2020)
The lacrimal gland (LG) is the main source of the tear film aqueous layer and its dysfunction results in dry eye disease (DED), a chronic immune-mediated disorder of the ocular surface. The desiccating stress (DS) murine model that mimics human DED, results in LG dysfunction, immune cell infiltration, and consequently insufficient tear production. To date, the immune cell kinetics in DED are poorly understood. The purpose of this study was to develop a murine model of intravital multi-photon microscopy (IV-MPM) for the LG, and to investigate the migratory kinetics and 3D morphological properties of conventional dendritic cells (cDCs). Mice were placed in a controlled environmental chamber with low humidity and increased airflow rate for 2 and 4 weeks to induce DED, while control mice were housed under standard conditions. DED mice had decreased tear secretion and increased fluorescein staining (p<0.01) compared to naïve controls. Histological analysis of the LG exhibited infiltrating mononuclear and polymorphonuclear cells (p<0.05) in DED mice compared to controls. Immunofluorescence staining revealed increased cDC density in DED (p<0.001). LG IV-MPM demonstrated increased cDC density in the LGs of DED mice, compared with controls (p<0.001). cDCs were more spherical in DED at both time points compared to controls (p<0.001); however, differences in surface area were found only at 2 weeks in DED compared with naïve controls (p<0.001). Similarly, 3D cell volume was significantly lower only at 2 weeks in DED vs. the naïve controls (p<0.001). 3D instantaneous velocity and mean track speed were significantly higher in DED compared to naive mice (p<0.001). Finally, the meandering index, an index for directionality, was significant increased at 4 weeks after DED compared with controls and 2 weeks of DED (p<0.001). Our IV-MPM study sheds light into the 3D morphological alterations and cDC kinetics in the LG during DED. While in naive LGs, cDCs exhibit a more dendritic morphology and are less motile, they became more spherical with enhanced motility during DED. This study shows that IV-MPM represents a robust tool to study immune cell trafficking and kinetics in the LG, which might elucidate cellular alterations in immunological diseases, such as DED.